Simulation for Upgrade Scheme Optimization of Campus Network - Zhu Kaiyu; Gao Xuefei; An Yongli; Liu Jiayu (Institute of Advanced Engineering and Science, 2013)
As a new network planning and design technique, the network simulation provides the objective and reliable reference for the network design, the network expansion, upgrade and optimization, thus the science of decision-making in network building is promoted. In this paper, we simulated campus users’ online behavior and actual network equipment operation by using OPNET, and carried on the simulation to the different scale and the different structure network, which obtained a group of simulation results. According to link utilization and end-to-end delay and other simulation results, we have analyzed the issue of influence campus network performance for designing the best network configuration, which has the important reference value for the planning and construction of the campus network. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3024